Survey On Radiation Awareness and Knowledge Among Malaysians in Johor, Malaysia - Mohd Zahar, Zurain; Sohaimi, Norhanna (International Journal of Allied Health Sciences, 2024)
Background: Members of public in Malaysia need to have knowledge and awareness regarding radiation and its associated risks to prevent misconception and misunderstanding about the information. This study aims to determine the existing level of radiation knowledge and awareness among Malaysians in Johor and to assess the public’s source of knowledge and information regarding radiation. Methods: A total of 384 respondents took part in this study. A set of questionnaire with a total of 21 questions and consists of two parts which are demographic data and radiation knowledge and awareness was distributed online by using Google forms. It was distributed through all online platforms including social media to reach out the respondents that lives in Johor. Results: The survey data was collected and analysed by using non-parametric tests which are Pearson chi-square and Kruskal-Wallis to see the relationship between demographic characteristics with the level of radiation knowledge and awareness. Based on the results, it demonstrate significant gaps in radiation awareness among Johor residents and identify demographics (e.g., health-related fields, workplace environment) associated with higher knowledge levels. The results underscore the importance of targeted educational outreach, especially through credible sources, to improve public understanding of radiation. Conclusion: The public need more disclosure towards the correct facts about radiation and its associated information. It is recommended that the general public obtain the correct information from reliable source to avoid misconception regarding radiation.